2013
DOI: 10.1002/cncr.28000
|View full text |Cite|
|
Sign up to set email alerts
|

Coregistered whole body magnetic resonance imaging‐positron emission tomography (MRI‐PET) versus PET‐computed tomography plus brain MRI in staging resectable lung cancer

Abstract: BACKGROUND:The objective of this study was to assess whether coregistered whole brain (WB) magnetic resonance imaging-positron emission tomography (MRI-PET) would increase the number of correctly upstaged patients compared with WB PET-computed tomography (PET-CT) plus dedicated brain MRI in patients with nonsmall cell lung cancer (NSCLC). METHODS: From January 2010 through November 2011, patients with NSCLC who had resectable disease based on conventional staging were assigned randomly either to coregistered M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0
5

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 22 publications
2
18
0
5
Order By: Relevance
“…Studies have shown through the used PET, and MRI brain scanning technology, those new neural cells are generated through life as well as new neural pathways [17] [18]. So, old brains are capable of creating measurable changes in brain organization.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown through the used PET, and MRI brain scanning technology, those new neural cells are generated through life as well as new neural pathways [17] [18]. So, old brains are capable of creating measurable changes in brain organization.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, lung cancer was correctly upstaged 25.9% (37 of 143 patients) in the PET/MRI group and 21.7% (26 of 120 patients) in the PET/CT plus brain MRI group. 69 Coregistered PET/MRI did not appear to help identify significantly more correctly upstaged patients than PET/CT plus brain MRI in patients with NSCLC. However, PET/CT plus brain MRI can improve the detection of brain metastases (32 of 442 patients; 7%) in comparison with PET/CT only.…”
Section: Stagingmentioning
confidence: 82%
“…FDG PET/BT'nin lenf nodu, kemik ve yumuşak doku metastazlarının saptanmasındaki yüksek doğruluk oranı ile klinik uygulanabilirlik kolaylığı, bu yöntemi akciğer kanseri olgularının değerlendirilmesinde ön planda tutmaktadır. Tüm vücut PET/MR'ın tüm vücut PET/BT + beyin MR görüntülemesi ile karşılaştırıldığı bir çalışmada iki görüntüleme protokolü arasında hasta evrelemesinde belirgin farklılık olmadığı belirtilmektedir (78).…”
Section: Akciğerkanserivepet/mrunclassified